2021
DOI: 10.3390/nano11092164
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle’s Toxicological Effects and Phytoremediation

Abstract: The advancement in nanotechnology has brought numerous benefits for humans in diverse areas including industry, medicine, and agriculture. The demand in the application of nanomaterials can result in the release of these anthropogenic materials into soil and water that can potentially harm the environment by affecting water and soil properties (e.g., soil texture, pH, organic matter, and water content), plants, animals, and subsequently human health. The properties of nanoparticles including their size, surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 158 publications
(150 reference statements)
1
25
0
Order By: Relevance
“…The inhibitory impacts of metallic NPs are apparent through its toxicity in plants. A number of research studies on plant-NPs interaction shows that NPs have both negative and positive effects, depending on the specific properties of NPs, their concentrations, reactivity, and plant species [141][142][143][144][145]. For instance, Lin and Xing [146] showed that seed supplemented with ZnO NPs at high concentration of 2000 mg L −1 negatively affected the germination of corn and ryegrass.…”
Section: Dose-dependent Variability Of the Nanoparticle Actionmentioning
confidence: 99%
“…The inhibitory impacts of metallic NPs are apparent through its toxicity in plants. A number of research studies on plant-NPs interaction shows that NPs have both negative and positive effects, depending on the specific properties of NPs, their concentrations, reactivity, and plant species [141][142][143][144][145]. For instance, Lin and Xing [146] showed that seed supplemented with ZnO NPs at high concentration of 2000 mg L −1 negatively affected the germination of corn and ryegrass.…”
Section: Dose-dependent Variability Of the Nanoparticle Actionmentioning
confidence: 99%
“…This sort of investigation would be crucial and supportive, and we need researchers dealing with nanoparticles for consideration of this feature leading to detailed studies related to uptake kinetics, buildup, and translocation of nanoparticles within the system directed, giving new vision and understandings about the application of bimetallic nanoparticles along with their consequences and harmfulness on organisms [ 166 ]. Straight linkage of this article for researches of upcoming time is necessary as well to remember that various species are taken as hyperaccumulation of silver and zinc oxide metal; their investigation and application in phytoremediation have been discovered, and a necessary amount of writings are accessible in the literature [ 167 ]. Though the similarity is not accurate about hyperaccumulation of metallic nanoparticles in living organisms, silver-zinc oxide nanoparticles would be the main component for documentation of mechanisms responsible for tolerance in stressful conditions and harmfulness of bimetallic nanoparticles [ 168 ].…”
Section: Trendsmentioning
confidence: 99%
“…Slow Ag + ion leaching is not harmful to normal cells—there are many studies available on this. On the other hand, slow Ag + ion leaching can be harmful to pathogens [ 36 , 37 , 38 ]; thus, AgNPs are useful as tissue-impedance lowering agents and as potential antimicrobial agents after radiofrequency ablation.…”
Section: Introductionmentioning
confidence: 99%